Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.molcel.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of IFN-γ Responses Is Fine-Tuned by DNA Architecture and the Non-coding Transcript of Ifng-as1

Abstract: Interferon gamma (IFN-g), critical for host defense and tumor surveillance, requires tight control of its expression. Multiple cis-regulatory elements exist around Ifng along with a non-coding transcript, Ifng-as1 (also termed NeST). Here, we describe two genetic models generated to dissect the molecular functions of this locus and its RNA product. DNA deletion within the Ifng-as1 locus disrupted chromatin organization of the extended Ifng locus, impaired Ifng response, and compromised host defense. Insertion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 71 publications
4
38
0
Order By: Relevance
“…The lncRNA TMEVPG1 (Theiler's murine encephalomyelitis virus persistence candidate gene 1) recently annotated as IFNG-AS1 (IFNG antisense RNA 1) was found to be downregulated in both HCV-and HDV-related HCC. This is in accordance with recent findings since IFNG-AS1 is transcribed antisense to IFNG, activating IFN-γ production, and the cellular response to viral infections by working as a chromatin structure modifier [122,139]. The three remaining lncRNAs, BC017743, BC043430, and LINC01152, are common to all viral etiologies.…”
Section: Lncrnas Related To Hcv-related Hepatocellular Carcinoma (Hcvsupporting
confidence: 92%
“…The lncRNA TMEVPG1 (Theiler's murine encephalomyelitis virus persistence candidate gene 1) recently annotated as IFNG-AS1 (IFNG antisense RNA 1) was found to be downregulated in both HCV-and HDV-related HCC. This is in accordance with recent findings since IFNG-AS1 is transcribed antisense to IFNG, activating IFN-γ production, and the cellular response to viral infections by working as a chromatin structure modifier [122,139]. The three remaining lncRNAs, BC017743, BC043430, and LINC01152, are common to all viral etiologies.…”
Section: Lncrnas Related To Hcv-related Hepatocellular Carcinoma (Hcvsupporting
confidence: 92%
“…and IFNG-AS1 is seen in long-lasting memory T cells, where high expression of IFNG-AS1 was associated with low IFNG suggesting that there may be feedback inhibition [30]. Here we observed that IFNG-AS1 genotype was associated with downstream effects on both the percentage of IFN--producing CD3 + T cells and the highly correlated percentage of TNF-…”
Section: Toxoplasma Gondii Infection By Reducing Ifng Expression Dismentioning
confidence: 53%
“…However, we found no evidence for expression of SERPINB10 in normal skin or in lesion biopsies, suggesting that a role in determining susceptibility to CL must be at the level of central regulation of haematopoiesis and/or immune responses. IFNG antisense RNA 1 encoded by IFNG-AS1 has been shown to finetune the magnitude of IFN- responses [30]. It is expressed in both mouse and human T helper1 cells and positively regulates Ifng expression [62,63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations